Theories of the End of the Novel - Barış Mete (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Compared to the other literary genres, the novel is the most recent form that emerged, for example, in English Literature with the rise of the bourgeoisie in the late eighteenth century. It was the work of Defoe, Richardson and Fielding in England in the same period of time that popularised the novel especially among the middle class readers. In contrast to the classical genres, particularly the epic, the novel was about common man. It depicted the everyday life of ordinary individuals. During the nineteenth century, the novel developed and became a fully established genre. It was the era of the most refined examples of the genre in English Literature. In the twentieth century, especially after the end of the Second World War, the novel became the subject of the discussions about a sense of an ending. It was openly argued that the genre would not have a future. It was claimed that the novel would soon be a deceased genre. Although all those pessimistic prognostications have failed to predict the future of the novel truly, it is essential to comprehend why a number of writers and literary theorists participated in the discussions.